Radicalizing Consciousness in the Dramas of Derek Walcott and Bate Besong - NCHIA, YIMBU EMMANUEL (Advances in Social Sciences Research Journal, 2016)
The postcolonial period in the Caribbean Island and Anglophone Cameroon continues to witness a deliberate and systematic betrayal of the hopes and aspirations of the citizenry, who in no small way fought very hard for the acquisition of political independence. This period was characterised by capitalist exploitation, with colonialist and their neo-colonial counterparts, who as a result of self interest, had transformed the lives of their people into a “perpetual nightmare”. This paper examines the extent to which slavery, oppression, exploitation, misery and corruption amongst other societal ills have eaten into the fabric of the Caribbean and Cameroonian societies and the manner in which the playwrights address and confront such burning societal mishaps. This paper also argues that the failure of independence to provide immediate solutions to the problems of the colonised people acted as a catalyst for the emergence of nationalist sentiments and open revolutions in most once colonised societies. From a Marxist critical paradigm, this paper reveals that Walcott and Besong are playwrights who hold strongly to the thesis that, morality and the doctrine of equal opportunity are treasured commodities that cannot be led loose on the hostile landscape of postcolonial dictatorship, oppression, exploitation and, above all, corruption. Thus, nationalism and social revolutions are considered, by the playwrights, as the panacea towards the complete emancipation of the impoverished masses from political, economic, social and cultural bondage.